2021
DOI: 10.3389/fonc.2020.602416
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Mechanisms of Breast Cancer Metastasis

Abstract: Breast cancer is one of the most common malignancy among women worldwide. Metastasis is mainly responsible for treatment failure and is the cause of most breast cancer deaths. The role of metabolism in the progression and metastasis of breast cancer is gradually being emphasized. However, the regulatory mechanisms that conduce to cancer metastasis by metabolic reprogramming in breast cancer have not been expounded. Breast cancer cells exhibit different metabolic phenotypes depending on their molecular subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 305 publications
(352 reference statements)
2
73
0
1
Order By: Relevance
“…Of all organs, the brain has the highest glucose demand and therefore favors enhanced glycolytic activity for energy production [88]. Accordingly, increased glycolysis has been observed in BCBM when compared with bone or lung metastatic tissue [89]. Interestingly, the metabolic phenotype also varies between the different molecular BC subtypes.…”
Section: Metabolic Phenotypementioning
confidence: 99%
“…Of all organs, the brain has the highest glucose demand and therefore favors enhanced glycolytic activity for energy production [88]. Accordingly, increased glycolysis has been observed in BCBM when compared with bone or lung metastatic tissue [89]. Interestingly, the metabolic phenotype also varies between the different molecular BC subtypes.…”
Section: Metabolic Phenotypementioning
confidence: 99%
“…Chemokines are low-molecular-weight signaling proteins (8-12 kDa) that can regulate many biological processes, including cellular immune response, glucose metabolism and angiogenesis (19)(20)(21)(22). Chemokines play important regulatory roles by binding to their specific receptors (23).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic deregulation can impact various molecular processes (e.g., cell proliferation, apoptosis, migration, and invasion) that contribute to tumor progression [44,[108][109][110] and influence cancer patient survival (Figure 2) [111].…”
Section: Multi-omics Studies Of Bc Prognosismentioning
confidence: 99%
“…Metabolic deregulation can impact various molecular processes (e.g., cell proliferation, apoptosis, migration, and invasion) that contribute to tumor progression [44,[108][109][110] and influence cancer patient survival (Figure 2) [111]. A number of studies have reported associations between metabolic alterations and BC patient survival based on single omic analysis, including genomic [112], transcriptomic [113], proteomic [46], and metabolomic [56,114,115] studies in tissue [46,112,113] and serum [56,114,115] samples.…”
Section: Multi-omics Studies Of Bc Prognosismentioning
confidence: 99%
See 1 more Smart Citation